CHANGING NATURE OF DANCE IN PRESENT SOCIETY: वर्तमान समाज में नृत्य का बदलता स्वरूप - Malaviya, Rekha (International Journal of Research -GRANTHAALAYAH, 2015)
The dance is a ritual performance of human expressions. It is a universal art, born with human life. The child cries as soon as he is born, hands and feet, expresses his feelings that he is hungry. The dance originated from these interactive acts which are well known. The dance started with spirituality. Initially the dance was performed in temples for devotion to God. With the changing times, during the Mughal period, it came out of temples and started being in the court of kings. Currently, the meaning of dance has changed further. Today dance has come on stage. The dance artist performs the stage, so that the common people enjoy it to its fullest. नृत्य मानवीय अभिव्यक्तियों का एक रसमय प्रदर्शन है। यह एक सार्वभौमिक कला है, जिसका जन्म मानव जीवन के साथ हुआ। बालक जन्म लेते ही रोकर, हाथ-पैर मारकर अपनी भावाभिव्यक्ति करता है कि वह भूखा है। इन्हीं आंगिक क्रियाओं से नृत्य की उत्पत्ति हुई जो सर्वविदित है। नृत्य का आरम्भ आध्यात्म से हुआ। प्रारम्भ में नृत्य मंदिरों में ईश्वर की भक्ति के लिये किया जाता था। बदलते समय के साथ ही मुगल काल में यह मंदिरो से निकलकर राजाओं के दरबार में होने लगा। वर्तमान में नृत्य के मायने और बदल गये है। आज नृत्य मंचो पर आ गया है। नृत्य कलाकार मंच प्रदर्शन करता है, जिससे जन सामान्य इसका पूर्णता से आनन्द लेते है।